2016
DOI: 10.1080/09687637.2016.1237475
|View full text |Cite
|
Sign up to set email alerts
|

Saying no to weed: Public opinion towards cannabis legalisation in Uruguay

Abstract: Aims: This research aimed to explore people's beliefs associated with opposition to cannabis legalisation in Uruguay. In 2014, Uruguay passed a national law regulating the production, sale and consumption of recreational marijuana. However, two-thirds of the Uruguayan public expressed disagreement towards the government's new policy. Methods: This study used logistic regressions on data from a national probabilistic sample of 1512 adults in Uruguay. Opinions and beliefs towards cannabis legalisation were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
1
15
0
4
Order By: Relevance
“…First, they show that acceptance of the cannabis law has increased in Uruguay, and that approval of the legislation is consistently higher among young people, residents of the capital, Montevideo, and especially among individuals with previous use of marijuana. These results complement what other studies have found in the early stages of the implementation of the law in Uruguay , and follow similar patterns found in other countries undergoing legalisation initiatives . They also suggest that changes in public opinion are occurring slowly.…”
Section: Discussionsupporting
confidence: 89%
“…First, they show that acceptance of the cannabis law has increased in Uruguay, and that approval of the legislation is consistently higher among young people, residents of the capital, Montevideo, and especially among individuals with previous use of marijuana. These results complement what other studies have found in the early stages of the implementation of the law in Uruguay , and follow similar patterns found in other countries undergoing legalisation initiatives . They also suggest that changes in public opinion are occurring slowly.…”
Section: Discussionsupporting
confidence: 89%
“…As regards the effects of individual or family income, (Degenhardt et al, 2008) find evidence that higher individual incomes are associated to higher consumption of all kinds of drugs, both legal and illegal. To the contrary, other studies find no evidence for income as a predictor in public support (Cruz et al, 2016: 5).…”
Section: Support For Drug Legalizationmentioning
confidence: 90%
“…Education is another key determinant. Individuals with higher studies are more likely to support drug legalization (Cruz et al, 2016). As regards the effects of individual or family income, (Degenhardt et al, 2008) find evidence that higher individual incomes are associated to higher consumption of all kinds of drugs, both legal and illegal.…”
Section: Support For Drug Legalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uruguay, public views towards cannabis liberalisation were intertwined with concerns about public security and apprehension that it will open the gate to heavier drugs (like amphetamines or opioids) rather than with concerns about individual health and demographic factors [34].…”
Section: Resultsmentioning
confidence: 99%